Hemoporfin-Mediated Photodynamic Therapy for Port-Wine Stains: Multivariate Analysis of Clinical Efficacy and Optical Coherence Tomography Appearance - Lin, Yanyan; Gong, Wei; Kang, Jie; Fang, Yuhong; Liu, Jingjing; Lin, Lihang; Xiao, Xuemin (Frontiers in Medicine, 2022)
Background Hemoporfin-mediated photodynamic therapy (HMME-PDT) is reported to be effective and safe for port-wine stains (PWS). However, its efficacy is influenced by several factors and there is no appropriate method to evaluate efficacy so far. Therefore, this study explored the clinical efficacy of HMME-PDT for PWS on the face and neck and the feasibility of evaluating treatment potency with optical coherence tomography (OCT). Methods A total of 211 PWS patients subjected to HMME-PDT were recruited for study and correlations of therapeutic effect with treatment sessions, age, gender, lesion distribution and treatment history analyzed. OCT was utilized for quantitative analysis of PWS lesions of 36 selected patients before and after HMME-PDT. Results The efficacy of two consecutive treatments was significantly higher than that of single treatment (P < 0.05). In multivariate analysis, after the first treatment, age, lesion distribution and treatment history were correlative factors affecting treatment efficacy (P < 0.05). The improvement effect on central facial lesions was lower than that on lateral facial lesions (P < 0.05). The efficacy of therapy on the group with no history of pulsed dye laser (PDL) treatment was greater than that on effective and ineffective treatment groups (P < 0.05). After the second session, age remained the only factor correlated with efficacy (P < 0.05). Dilated vessel diameter and depth before and after treatment were significantly different (P < 0.05). With increasing treatment times, age was the most significant factor influencing treatment efficacy. Conclusions Our collective findings indicate that HMME-PDT therapy is effective and safe for PWS and support the utility of OCT in objective assessment of the efficacy of HMME-PDT.